2013
DOI: 10.1103/physrevd.87.045018
|View full text |Cite
|
Sign up to set email alerts
|

Gauge field localization on the Bloch brane

Abstract: We present new results on the localization of gauge fields in thick brane models. The fourdimensional observable universe is considered to be a topological defect which is generated by two scalar fields coupled with gravity embedded in a five-dimensional space-time. Like other thick brane models, the Bloch brane setup is not capable of supporting gauge field localization. In order to circumvent this problem we include the dilaton field and, as a result, obtain normalizable solutions. In addition, by writing th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 45 publications
(86 reference statements)
0
53
0
Order By: Relevance
“…The double sine-Gordon potential (DSG) provides twokink solutions that can be used to model thick branes [7,[45][46][47][48][49]. Previous works have showed that splitting branes with internal structure, generated by two-kink defects, can foment the presence of resonant states [13][14][15]. Based on these results we now propose to construct a brane model generated by a DSG potential with the presence of the dilaton field.…”
Section: Double Sine-gordon Branementioning
confidence: 99%
See 2 more Smart Citations
“…The double sine-Gordon potential (DSG) provides twokink solutions that can be used to model thick branes [7,[45][46][47][48][49]. Previous works have showed that splitting branes with internal structure, generated by two-kink defects, can foment the presence of resonant states [13][14][15]. Based on these results we now propose to construct a brane model generated by a DSG potential with the presence of the dilaton field.…”
Section: Double Sine-gordon Branementioning
confidence: 99%
“…Thus, we need to investigate the effects of solution U (y) due to (13) to evaluate the existence of vector modes in the brane. The effective action (15) immediately tells us that the warp factor is absent and its exponential suppression effect no longer applies.…”
Section: Gauge Field Zero Modementioning
confidence: 99%
See 1 more Smart Citation
“…3 offer explicit possibilities to implement the hybrid Bloch brane scenario, and the results open up new issues, such as the ones investigated before in the case of the Bloch brane, namely the study of degeneracy and criticality, fermion localization, gauge field localization, and graviton resonances [15][16][17][18][19][20][21][22][23]25,26]. We end our work in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…[14] the authors suggested a brane scenario described by two real scalar fields coupled with gravity, the second field contributing to propitiate internal arrangement, implementing therefore the so-called Bloch brane model. This framework was then explored by several authors in different situations, such as in the study of criticality and degeneracy, fermion localization, gauge field localization, graviton resonances, and so forth [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%